The Role of Teachers in the Application of Digital Literacy to Create a Digital Literate Generation - Hendrarso, Panji; Habib, Md. Ahsan (Technium Social Sciences Journal, 2022)
Entering the era of the industrial revolution 4.0, especially the world of education, schools, teachers and students live in an advanced digital world. In this regard, the existence and role of teachers is very important for digital literacy. In today’s conditions, the role of the teacher is very necessary, as it is known that the content on the internet is almost unlimited with a variety of information with an abundance of volume, while teachers and parents cannot always control internet access by students at all times. This study aims to answer the question of how digital literacy is implemented in schools and what are the obstacles faced by teachers in teaching digital literacy. This is a qualitative research with a phenomenological approach. Data collection was obtained from in-depth interviews with 20 teachers. This research shows that there are still many teachers who have not had the opportunity to take part in training related to digital literacy, both organised by the government and the private sector. Therefore, teachers are expected to be proactive in seeking information related to digital literacy from various sources. This study also proves that socialisation related to digital literacy is still very lacking. The government and related parties must be more intensive in conducting socialisation so that the community, especially parents, also understands the importance of digital literacy.